Effect of lactylation on functional and structural properties of gluten - Wang, Yu; Li, Yan; Fan, Mingcong; Wang, Li; Qian, Haifeng (Frontiers in Nutrition, 2022)
Gluten is widely used as a high-quality protein material in the food industry, however, low solubility restricts its development and applications. In this study, gluten was treated with lactate and sodium lactate for lactylation. Lactylation of gluten altered surface charges of the protein, leading to a significant improvement in the solubility. An improvement in oil absorption capacity (OAC) could be attributed to a decrease in protein folding degree after lactylation. In addition, the emulsifying properties of gluten were significantly enhanced. The introduction of lactate group also significantly increased the viscoelasticity of gluten. Fourier transform infrared spectroscopy (FTIR) showed there was a significant decrease in β-turns content and a significant increase in β-sheets content. The folded conformation of gluten was gradually extended after lactation by fluorescence spectroscopy measurement. Both in lactate and sodium lactate treatment, the maximum emission wavelength indicated a blue shift, and the UV intensity showed an increase. These results could demonstrate that lactylation could extend the structure and improve the functional property.